Rethinking international financial centres through the politics of territory: Renminbi internationalisation in London’s financial district - Hall, Sarah (Wiley, 2016)
This paper revisits canonical thinking on international financial centres (IFCs) that understands them as being primarily sustained through: market liquidity; economies of competition and cooperation between financial and related professional services; and acting as interpretative nodes within global finance. In contrast, I explore the implications of foregrounding questions of power and politics in the (re)production of IFCs. Drawing on the case of the development of offshore renminbi markets in London’s financial district, I argue the state plays a vital, yet comparatively neglected, role in shaping the development and changing nature of international financial centres. In so doing, the paper calls for work in economic geography and cognate social sciences to understand finance as a political as well as an economic, social and cultural relation.